Enhancing Grade 4 Learning Outcomes through Character Education-Based Comic Media: Meningkatkan Hasil Belajar Kelas 4 melalui Media Komik Berbasis Pendidikan Karakter - Khasanah, Ari Uswatun; Tirtoni, Feri (Universitas Muhammadiyah Sidoarjo, 2023)
This study addresses the pressing issue of low learning outcomes in the context of grade 4 character education. Employing a quantitative pre-experimental design known as the One-Shoot Case Study, this research investigates the efficacy of character education-focused comic media on learning outcomes. The study encompasses a sample of 24 elementary school students and employs a multiple-choice posttest to measure learning outcomes. The data analysis, facilitated by SPSS software version 22, applies a one-sample t-test, revealing a significant influence of character education-based comic media (t = 6.789, p < 0.001) on the learning outcomes of grade 4 students. The outcomes underscore the potential of innovative pedagogical tools in enhancing education quality, with implications for curriculum development and instructional design. Highlights: Innovative Pedagogy: Employing character education-based comic media to enhance learning outcomes in grade 4 education. Quantitative Assessment: Utilizing a pre-experimental design and one-sample t-test to analyze the impact of comic media on student performance. Significant Influence: Demonstrating a notable improvement in learning outcomes, emphasizing the potential of creative educational tools. Keywords: Character education, comic media, learning outcomes, elementary school, pedagogical innovation.